POTENSI DAN PROGRAM “MAHKOTA” BADAN AMIL ZAKAT NASIONAL (BAZNAS) SUMATERA SELATAN - Zainuddin, Cholidi; Hadi, Abdul (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The economic state of being a barrier between the poor and the rich is a necessity, but the distance between the two poles too far could cause problems in human life. Moreover, the living conditions, whether rich or poor or the needy can be counted on in the hereafter. Nevertheless, completely eliminating poverty and the poor on earth become utopian, but managing poverty should be done. Therefore, the effort to bring the two human groups together must be continuously done; mutual benefit effort between human beings will happen and be handled. One of the real efforts and controlling and protecting the human being is zakat. With the charity of the rich will help people who are weak in the economic field in order to achieve a position in life, a better life and quality. This article provides a mapping of potential and flagship programs of Badan Amil Zakat Nasional Sumatera Selatan.